Mitf cooperates with Rb1 and activates p21Cip1 expression to regulate cell cycle progression. - Carreira, S; Goodall, J; Aksan, I; La Rocca, SA; Galibert, MD; Denat, L; Larue, L; Goding, C (2005)
The controls that enable melanoblasts and melanoma cells to proliferate are likely to be related, but so far no key regulator of cell cycle progression specific to the melanocyte lineage has been identified. The microphthalmia-associated transcription factor Mitf has a crucial but poorly defined role in melanoblast and melanocyte survival and in differentiation. Here we show that Mitf can act as a novel anti-proliferative transcription factor able to induce a G1 cell-cycle arrest that is dependent on Mitf-mediated activation of the p21(Cip1) (CDKN1A) cyclin-dependent kinase inhibitor gene. Moreover, cooperation between Mitf and the retinoblastoma protein Rb1 potentiates the ability of Mitf to activate transcription. The results indicate that Mitf-mediated activation of p21Cip1 expression and consequent hypophosphorylation of Rb1 will contribute to cell cycle exit and activation of the differentiation programme. The mutation of genes associated with melanoma, such as INK4a or BRAF that would affect either Mitf cooperation with Rb1 or Mitf stability respectively, would impair Mitf-mediated cell cycle control.